2015
DOI: 10.2215/cjn.10871014
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acidosis in a Patient with Type 2 Diabetes Mellitus

Abstract: Lactic acidosis occurs when lactate production exceeds its metabolism. There are many possible causes of lactic acidosis, and in any given patient, several causes may coexist. This Attending Rounds presents a case in point. Metformin's role in the pathogenesis of lactic acidosis in patients with diabetes mellitus is complex, as the present case illustrates. The treatment of lactic acidosis is controversial, except for the imperative to remedy its underlying cause. The use of sodium bicarbonate to treat the oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…In this respect, Mandel et al [ 67 ] found that adjusting primary results according to animal-derived protein and potassium intake resulted in no attenuation in the association between plasma bicarbonate and diabetes, suggesting that these underlying mechanisms may be independent of dietary acid load. Furthermore, available evidence does not allow for inference on the relationship cause and effect: metabolic disturbances such as diabetes itself can affect pH status and the production of acid species [ 74 , 75 ] by affecting metabolic reactions and kidney functionality [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Mandel et al [ 67 ] found that adjusting primary results according to animal-derived protein and potassium intake resulted in no attenuation in the association between plasma bicarbonate and diabetes, suggesting that these underlying mechanisms may be independent of dietary acid load. Furthermore, available evidence does not allow for inference on the relationship cause and effect: metabolic disturbances such as diabetes itself can affect pH status and the production of acid species [ 74 , 75 ] by affecting metabolic reactions and kidney functionality [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is continuously detected in fake slimming formulations [57], because unlike sulfonylureas, it does not cause hypoglycaemia nor hyperinsulinemia even when administered alone in healthy subjects or patients with type 2 diabetes [58]. In some instances, however, metformin, like its withdrawn structural analogues buformin and phenformin, is known to cause lactic acidosis as a result of the very minimal liver uptake of serum lactate which is a required substrate of gluconeogenesis [59,60].…”
Section: Metforminmentioning
confidence: 99%
“…In addition, even CKD patients with minimal renal impairment but the presence of microalbuminuria or proteinuria can easily develop acute kidney injury (AKI) independent of the natural progression and/or severity of their underlying renal insufficiency (16,17). Metformin-associated lactic acidosis is rare but not nonexistent, highlighted by a recent case record in the New England Journal of Medicine (5) as well as other case reports (7,18,19), including a 2010 case series (20). The case series compared metformin-associated acidosis with other types of lactic acidosis, such as postcardiac arrest, septic shock, cardiogenic shock, mesenteric ischemia, and hemorrhagic shock, none of which had a blood pH below 7.0 except for metformin-associated acidosis (20).…”
Section: Is Metformin-associated Lactic Acidosis Real?mentioning
confidence: 99%